Mobilization of CD11b+/Ly6chi monocytes causes multi organ dysfunction syndrome in acute pancreatitis - Wilden, Anika; Glaubitz, Juliane; Otto, Oliver; Biedenweg, Doreen; Nauck, Matthias; Mack, Matthias; Ribback, Silvia; Bröker, Barbara M.; Rheinbaben, Sabrina Freiin von; Lerch, Markus M.; Aghdassi, Ali Alexander; Weiss, Frank Ulrich; et al. (Frontiers in Immunology, 2022)
Objective: Acute pancreatitis (AP) is an inflammatory disorder, the severe form of which is burdened with multi-organ dysfunction and high mortality. The pathogenesis of life –threatening organ complications, such as respiratory and renal failure, is unknown. Design: Organ dysfunction was investigated in a mouse model of AP. The influence of monocytes and neutrophils on multi organ dysfunction syndrome (MODS) was investigated in vivo by antibody depletion. Using real-time-fluorescence and deformability-cytometry (RT-DC) analysis we determined the mechanical properties of neutrophils and monocytes during AP. Furthermore, blood samples of pancreatitis patients were used to characterize severity-dependent chemokine profiles according to the revised Atlanta classification. Results: Similar to AP in humans, severe disease in the mouse model associates with organ dysfunction mainly of lung and kidney, which is triggered by a mobilisation of Ly6g-/CD11b+/Ly6c hi monocytes, but not of Ly6g+/CD11b+ neutrophils. Monocyte depletion by anti-CCR2 antibody treatment ameliorated lung function (oxygen consumption) without interfering with the systemic immune response. RT-DC analysis of circulation monocytes showed a significant increase in cell size during SAP, but without a compensatory increase in elasticity. Patient chemokine profiles show a correlation of AP severity with monocyte attracting chemokines like MCP-1 or MIG and with leukocyte mobilisation. Conclusion: In AP, the physical properties of mobilized monocytes, especially their large size, result in an obstruction of the fine capillary systems of the lung and of the kidney glomeruli. A selective depletion of monocytes may represent a treatment strategy for pancreatitis as well as for other inflammation-related disorders.